Neotype designation of the Short-tailed Albatross Phoebastria albatrus (Pallas, 1769) (Aves: Procellariiformes: Diomedeidae) - Yamasaki, Takeshi; Eda, Masaki; Schodde, Richard; Loskot, Vladimir (Zootaxa, 2022)
The Short-tailed Albatross Phoebastria albatrus (Pallas, 1769) is a threatened seabird widely distributed in the northern Pacific Ocean with its largest breeding sites on the Senkaku Islands and Torishima Island, Japan, which are separated by over 1700 km. A recent taxonomic revision based on morphological, behavioral, and DNA sequence evidence has revealed that this species consists of two cryptic species: a smaller species which breeds mainly in the Senkaku Islands, and a larger species which breeds mainly on Torishima Island. However, it has remained unclear to which of these species the scientific name Phoebastria albatrus applies, because the type specimens are lost. Here a neotype is designated to resolve this taxonomic issue. From now on, the scientific name Phoebastria albatrus should be applied only to the smaller species breeding on the Senkaku Islands. The name of the larger species is more problematic, as the types of each synonym of P. albatrus must be traced, found, and examined.